IMITATION MODEL OF FORECASTING QUALITY OF JOINTS AT WELDING BY NOT ADAPTIVE ROBOTS - U.G. LUDMIRSKY; V.F. LUKJANOV; S.V. JAK (Advanced Engineering Research)
The factors influencing quality of welded joints, executed by not adaptive robots, are presented. The imitating model of forecasting of quality welded joints is developed. The model allows to reveal influence of dominating factors and to define ways of perfection of technology of the robotized welding.